ANALISIS TANTANGAN DALAM PENYUSUNAN RANCANGAN UNDANG- UNDANG DI ERA TRANSFORMASI DIGITAL: ANTARA REGULASI, INOVASI, DAN PERLINDUNGAN HAKAkhmad Zaki Yamani - Akhmad Zaki Yamani (INTELIGENSIA MEDIA, 2025)
The rapid development of digital technology has had a significant impact on social, economic, and legal life. However, the main challenge in drafting regulations in the digital era is the difficulty in balancing the need for innovation with the protection of individual rights. This article examines various challenges in digital regulation, such as slow legislative processes, a lack of technical understanding among policymakers, and reliance on rapidly changing technology. The article also provides recommendations for more adaptive regulatory strategies, including the application of risk-based regulations, strengthening data privacy protection, and emphasizing the importance of collaboration between policymakers and the technology sector. Additionally, the article highlights the importance of public participation in the digital legislative process and the role of education in enhancing policymakers' understanding of technology issues. With the right approach, digital regulation can create an ecosystem that supports innovation, protects individual rights, and is responsive to technological developments.